Compounded Formulations of Dimethyl Fumarate Show Significant Variability in Product Characteristics - Boulas, P. (Drug Research, 2016)
Background: Pharmacy compounded products are not regulated to the same standards as commercially available, approved products, increasing potential safety and efficacy risks to patients. This report describes an in vitro study examining consistency of content and release profile of compounded dimethyl fumarates.Methods: Samples of compounded dimethyl fumarate (cDMF-A, cDMF-B, cFumaderm) from separate Austrian compounding pharmacies were analyzed for drug content, uniformity of dosage, impurity, and in vitro release.Results: The average dimethyl fumarate (DMF) content ranged from 102.5 to 96.7% of the 120 mg content listed on the product labels. While the DMF capsule-to-capsule content of cDMF-A was somewhat uniform (~20% difference), there was greater variability amongst cDMF-B and cFumaderm capsules (> 30% difference). Impurity testing revealed 2 and 4 unknown components within cDMF-A and cDMF-B, respectively, with levels ranging from 0.05 to 0.81% of total drug content. In in vitro testing of cDMF-A,>10% (12 mg) of DMF was released after 120 min in simulated gastric fluid and 17% (20 mg) released in simulated intestinal fluid after 60 min. While minimal amount of DMF was released from cDMF-B in simulated gastric fluid, 50% (60 mg) of DMF was released after 60 min in simulated intestinal fluid. Similarly for cFumaderm, a fraction (< 20 mg) of the 120 mg target dose was released after several hours in simulated intestinal fluid. The uniformity of release rates across capsules varied significantly.Conclusion: These results demonstrate that compounded fumarates are not equivalent to licensed products and may present unknown safety, efficacy, or quality risks.
Keywords: anti-inflammatory drugs; drug research; bioavailability